GRADE II CHILD ASTROCYTOMA AND FACIAL MIMIC DEFICT - Santos, Carla C. Tomazolli (2018)
The Astrocytoma is a type of brain cancer that originates from astrófitos, brain cells that surround nerve cells supporting the neurons, characterized by low grade of malignancy, your are brain tumors of origin astrocitárias, which are the most common form of cancer in childhood, responsible for approximately 20% of all intracranial tumors of this age group. 8 are also known as gliomas, involving a series of intracranial tumors, have a high level of complexity due to numerous cell type involved and can be subdivided into focal or diffuse that refer to tumors that originate in the cells glial (oligodendrocytes, astrocytes, microglia, and ependymal). Are classified as grade I, IV with a variance in your level of malignancy from smallest to largest. The study of literary review was based on the Scielo search platform. In order to systemize data collected by linking theoretical categories from authors with clinical reports.